A New Multicriteria Approach for the Efficiency Measures on the Forex Market - Przemyslaw Juszczuk; Lech Krus (IEEE Access)
This paper presents a multi-criteria optimization approach for decision support in the forex market. Decision-makers using technical analysis encounter numerous signals generated by market indicators across various instruments—currency pairs. However, typical online trading systems often lack the capability to validate these signals within a multi-criteria space. This paper introduces a system concept that evaluates signals according to different efficiency measures. A corresponding multi-criteria optimization problem is formulated and solved to select only Pareto-optimal decision variants concerning these efficiency measures. The proposed concept has been implemented using different efficiency measures in an experimental computer-based system and tested through numerical experiments, yielding positive results.